Experiment of Polarization Forces in Scanning Electrostatic Force Microscopy for Measuring Surface Profile of Dielectric - He, Gaofa; Jia, Zhigang; Ito, So; Shimizu, Yuki; Gao, Wei (The open electrical and electronic engineering journal, 2014)
For measuring the surface profile of many micro-optical components with complicated shapes, which are made of non-conductive material, the electrostatic force microscopy (EFM) was recommended. The relationship between the polarization force and the tip-to-sample distance was analyzed based on dielectric polarization theory. The prototype of the scanning electrostatic force microscopy was built. The force curves of different samples with different materials and surface shapes were detected by the EFM prototype. Both theoretical analysis and the experimental results demonstrated that the EFM system can be used to measure the surface profile of non-conductor.